Killers that Once Were Humans: Reading the Role of Modern Law Via Instrumental Rationality - Hassan, Momen Abdelbari (AUC Knowledge Fountain, 2024)
For Max Weber, the process of modernization is the process of rationalization in which it includes every realm in our modern life, such as the economy, science, organization, education, and law. However, this kind of rationalization has created coercive and inhumane conditions because rationalization has converted to being instrumental (value-free) without regard to any transcendental or moral values. The inhumane paradigm has become the only fate of our world. The vision needs rational domination to be achieved through formal rational law. Modern law, along with bureaucratization, has paved the road to rational political domination. This kind of domination captures human minds and makes them small cogs who function and serve this instrumental paradigm. This paper argues that instrumental rationality implicates humans in its bloody crimes. Human beings, both officials and ordinaries, bear guilt because they have become partners in their states’ crimes.